Effects of Neoadjuvant Fluorouracyl-Adriamycin- Cytoxan (FAC) Chemotherapy Response to CD4 + Serum Levels In Breast Cancer - Legiran; Ade Permana; Benny Kusuma; Nur Qodir (Sriwijaya Journal of Surgery, 2018)
Introduction. CD4+ T-helper has an important role in immune system modulation especially to maintain long-term anti tumor effect. CD4+ also serves to activate CD8+ for destroyed the tumor cells. It was expected there were role of immunity on tumor growth and response of breast cancer chemotherapy to CD4+ levels serum. Furthermore, this study was aimed to investigate the effects of neoadjuvant chemotherapy on CD4+ levels in patients with locally advanced breast cancer at General Hospital Dr. Mohammad Hoesin Palembang. Method. This study was a non-comparable clinical trial by looking at serum CD4+ levels in patients with locally advanced breast cancer before and after neoadjuvant chemotherapy. Results. Of the 30 subjects the subject age ranged from 33-66 years with an average of 45 years. There were 17 patients with contraception history (56.7%), 13 patients with family history of breast cancer (43.3%). From this study, it was obtained 23 patients with good chemotherapy response (76.7%) and there were 7 patients who had poor chemotherapy response after neoadjuvan chemotherapy (23.3%). Paired t-test analysis showed that there was a significant difference in mean CD4+ count before and after neoadjuvan chemotherapy. At the CD4+ level before chemotherapy 775.55 had a sensitivity of 60% and a specificity of 57% (cut of point). While CD4+ levels after chemotherapy 470.85 with sensitivity of 60% and specificity of 57%. Conclusion. CD4+ pre-chemotherapy examination had a sensitivity score of 60% and a specificity of 57% in predicting neoadjuvant chemotherapy response.